Effect of BCG vaccination on cytokine mRNA expression in atopic children with asthma - ÖZER, SIDIKA AYŞE (My University, 2003)
BACKGROUND: To investigate whether a preexisting T(H2)-type immune response could be suppressed by BCG immunization in atopic children with asthma. METHODS AND RESULTS: We have used PCR to amplify reverse transcribed (RT) IFN-gamma and IL-5 mRNA expressed by peripheral blood mononuclear cells (PBMCs) in response to in vitro phytohemagglutinin A, purified protein derivative and Dermatophagoides pteronyssinus II stimulation from nine atopic children, both before and 8 weeks after BCG vaccination. We have demonstrated that IFN-gamma expression was induced in response to all stimulants (IFN-gamma/beta-actin) after the vaccination, whereas there was no expression before (P<0.001). Although there was a tendency to diminish in the expression of IL-5 mRNA in response to the stimulants, only PHA rendered a statistically significant decrease after the vaccination. CONCLUSIONS: These results provide some evidence of TH1 dominance after BCG administration in atopic children.
Keywords: Humans; Animals; Child; Cytokines; Asthma; Tuberculin; Hypersensitivity, Immediate; BCG Vaccine; Leukocytes, Mononuclear; Phytohemagglutinins; Gene Expression; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Antigens, Dermatophagoides; Immunoblotting